Restoration Of Minor Defects in the Dental Row Using Prosthetics. - Khamidova Guli Komilovna (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Restoration of minor defects in the dental row is a critical concern in modern prosthodontics as such defects impair both function and aesthetics. Specific Background: With advances in material science, zirconia-based and other metal-free restorations have emerged as superior alternatives to traditional metal-ceramic systems due to their enhanced biocompatibility, mechanical strength, and optical properties. Knowledge Gap: However, there remains limited clinical evidence concerning the biological and functional efficacy of zirconia-based prostheses in managing small-scale dental defects, particularly regarding periodontal responses and long-term stability. Aims: This study aimed to evaluate the clinical performance, marginal adaptation, periodontal health, and aesthetic outcomes of zirconia-based restorations compared with press-ceramic and metal-ceramic systems. Results: Findings revealed that zirconia restorations achieved 100% Alpha ratings for marginal adaptation, color stability, and absence of postoperative sensitivity, alongside stable Papillary Bleeding Index (PBI) and Sillness-Loe scores over 12 months, indicating superior tissue compatibility. Novelty: The study introduced a CAD/CAM-assisted, minimally invasive restorative approach that integrates digital precision with biological harmony. Implications: These results substantiate zirconia-based prosthetics as a biologically and functionally optimal solution for minor dental defects, providing a foundation for patient-specific, digitally guided protocols in modern prosthodontic rehabilitation.Highlight : Zirconia-based restorations showed better marginal adaptation, color stability, and tissue compatibility. The study confirmed the periodontal stability and biocompatibility of zirconia materials in minor defect restoration. The use of CAD/CAM technology improved precision and customization in prosthetic fabrication. Keywords : Zirconia Forms of Restoration, Prosthetic Dentures, Computer Aided Design/Computer Aided Manufacturing, Periodontal Care, Biocompatibility